RATIONAL CHOICE THEORY: GREEN BANKING PRACTICES FOCUSED - Fendy Cuandra; Ivan Jones; Candy; Egabetha Amirah Yudhaputri; Stefhani Susanto (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
Banks as economic drivers in their own country have a high influence on encouraging environmentally friendly practices. It is due to the increasing damage to the environment in Indonesia. Before the 2010s, banks did not have enough awareness to carry out environmentally friendly practices included in their operational activities. In Indonesia, the government started to enforce green banking rules in 2012. Indonesia initiated green banking practices, which reached their peak in 2020 during the COVID-19 pandemic. This study examines whether customers have understood the growth of green banking practices in Indonesia, the effects of banks' environmentally friendly practices on the loyalty of commercial bank customers, and whether awareness and knowledge of banks' green practices will have an impact on loyalty towards banks. This study examines the importance of implementing green banking due to the increasing awareness and high level of customer knowledge about the environment. This research is the first to be conducted in Batam City, examining green banking through the lens of the grand theory of rational choice. The rational choice theory will serve as the novelty for this research. Also, the green trust variable mediating green banking awareness and green banking knowledge affecting green banking loyalty will serve as the novelty of this research.